Highly Enhanced Force Generation of Ionic Polymer-Metal Composite Actuators via Thickness Manipulation - Park, Jong Hyuk; Lee, Sung Won; Song, Dae Seok; Jho, Jae Young (American Chemical Society, 2015)
On purpose to enhance the generating force of ionic polymer-metal composite (IPMC) actuators, the thickness of the ion-exchange membrane is manipulated in two different ways. One is grafting poly(styrenesulfonic acid) onto poly(vinylidene fluoride-co-hexafluoropropylene) films with varying thickness, and the other is stacking pre-extruded Nafion films to thicker films by pressing at high temperatures. For both groups of the membranes, ionic properties including ion-exchange capacity and ionic conductivity are maintained similarly inside the groups regardless of the thickness. The actuation tests clearly show the increase in generating force with increasing thickness of the IPMCs prepared. It is due to a larger bending stiffness of thicker IPMCs, which is consistent with the predicted result from the cantilever beam model. The increase in force is more remarkable in Nafion-stacked IPMCs, and a thick IPMC lifts a weight of 100 g, which far exceeds the reported values for IPMCs.
Keywords: SULFONATED POLY(VINYLIDENE FLUORIDE); HIGH-ENERGY RADIATION; ARTIFICIAL MUSCLES; EXCHANGE MEMBRANES; BIOMIMETIC SENSORS; NAFION MEMBRANES; IPMC ACTUATORS; PERFORMANCE; FLUOROPOLYMERS; STYRENE